Rare-Earth based magnesium alloys as a potential biomaterial for the future - Abhishek Kumar; Amit Choudhari; Ashish Kumar Gupta; Avinash Kumar (Journal of Magnesium and Alloys)
Magnesium (Mg) is renowned for its unique combination of low weight, high strength-to-weight ratio, biocompatibility, and natural abundance, positioning it as an ideal candidate for biodegradable implants in biomedicine. Despite these advantageous properties, challenges such as poor formability and susceptibility to corrosion have restricted its broader application. This review critically addresses these limitations by delving into Mg's biodegradation mechanisms and the various degradation modes activated by different physiological environments. Emphasis is placed on understanding these processes to optimize Mg's utility as a biomaterial. Additionally, the transformative potential of integrating rare-earth (RE) elements into Mg alloys is explored. These elements significantly refine the microstructure, enhance mechanical properties, and improve corrosion resistance, effectively mitigating some of Mg's inherent limitations. Rare earth elements (REEs) significantly improve the mechanical properties of magnesium alloys. Cerium and lanthanum form protective oxide layers, reducing corrosion. Neodymium prevents hydrogen embrittlement, while yttrium refines grain size. The combination of REEs offers a diverse range of properties, including enhanced strength, creep resistance, high-temperature performance, corrosion resistance, ductility, and toughness. This versatility allows for tailored alloy selection for specific applications. The review also assesses the effects of various RE elements on biodegradability, cytotoxicity, and biological interaction, which are crucial for medical applications. Furthermore, the innovative realm of additive manufacturing (AM) is investigated to develop efficient Mg-RE-based biomedical implants, enabling the precise customization of implants to meet individual patient needs. Through a comprehensive evaluation of the latest research, this study projects the promising future of Mg-RE alloys as groundbreaking biomaterials poised to redefine medical implant technology with their superior mechanical and biological properties.